L1 – L2 semantic and syntactic processing: The influence of language proximity. (November 2018) - Booth, Paul; Clenton, Jon; Van Herwegen, Jo
Abstract: This study examined the extent to which a first language (L1) influences a second language (L2). We explored this potential influence by evaluating participant responses for semantic and syntactic word strings composed from the 1K British National Corpora word list. We investigated two different first language groups, and assessed their responses to semantic and syntactic judgement tasks in their L2 (English), alongside an English control group. The participants were L1 Japanese (n = 23), L1 Italic Indo-European (n = 25), and L1 English (n = 25). Each subject was asked to judge 60 semantic word strings, and 60 syntactic word strings. We then compared each of the three groups for accuracy and response time, with the L1 English group acting as the control. Results indicated significant differences which we suggest might relate to L1 background influences. The L1 Japanese participants responded less accurately to semantic judgements compared to L1 Italic Indo-European counterparts, while there was no significant difference between the two L2 learner groups for syntactic accuracy. The L1 Japanese participants were also slower than their L1 Indo-European counterparts for both semantic and syntactic word strings. We discuss our findings in relation to recent bilingual models of lexical development.